Mapping the Path to Teacher Success: Understanding the Dimensions of Passion in Education among Iranian EFL Teachers - Zohreh Sisiyan; Fazlollah Samimi; Shahram Afraz (Iranian Journal of Educational Research)
Objective: This study investigates the relationship between teachers' passion and their success in English as a Foreign Language (EFL) instruction in Bandar Abbas, Iran, aiming to understand how various dimensions of teachers' passion impact their effectiveness in the classroom. Methods: Data were collected from 200 EFL educators using validated survey instruments. The study employed correlation and regression analyses to assess the relationship between teachers' passion scores and classroom success. The survey examined dimensions such as learner characteristics, organizational dimension, psychological characteristics, professional features, and individual characteristics. Results: The analysis revealed a moderate positive correlation (R=0.625) between teachers' passion scores and classroom success. The regression model explained 39.1% of the variation in teachers' success, highlighting the significance of teachers' passion as a predictor. Among the factors, learner characteristics were the most influential, followed by organizational dimension, psychological characteristics, professional features, and individual characteristics. The absence of significant collinearity between independent variables validated the regression model, indicating that each dimension of teachers' passion contributes uniquely to predicting their success. Conclusions: The study underscores the crucial role of teachers' passion in shaping educational outcomes and suggests fostering a culture of passion and professional development among educators. It highlights the importance of supportive organizational environments and targeted professional development programs. By exploring the emotional dynamics of teaching, this research contributes to the broader discourse on teacher effectiveness, emphasizing the interplay between teachers' emotions, identity, and student perceptions. These findings have significant implications for educational policy and practice, particularly in enhancing teacher motivation and effectiveness.